(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2025)
Sex education is a crucial topic in human life. However, its importance in discussing, understanding, and studying it is often overlooked. It is argued that the topic of sexuality should be addressed at home, because the family plays a fundamental role in the upbringing of its children. The sex education received at home, the family environment, and the values ​​and beliefs transmitted by caregivers—whether parents, grandparents, aunts, or uncles—can influence how a person perceives and experiences their sexuality. However, counseling professionals must understand and promote effective communication between caregivers and students, fostering an atmosphere of trust and openness for discussing sexuality. This allows family members to express their doubts, concerns, and feelings honestly and receive appropriate guidance. Thus, in the Bachelor of Science in Education program with an emphasis in Guidance Counseling at the University of Costa Rica, the objectives of the Guidance and Sexuality course were readjusted. In this course, the evaluation rubric requires students to design sexuality education strategies based on the disciplinary knowledge of Guidance Counseling, for individuals at various stages of the life cycle. Therefore, a compilation of the topics covered in the lesson plans developed by students during the years 2021, 2022, and 2023 is presented.